Dyslexia: from myths to scientific knowledge, for inclusive education - Fernandes, Ana Matos (2024)
Dyslexia is a specific learning difficulty in reading that has a neurobiological origin and is characterized by difficulties in the correct and/or fluent re poor spelling and decoding skills, with consequences for reading comprehension. These consequences extend beyond reading and the study compromise cross-curricular learning and a child or young person's entire school career. Nowadays, some myths and misconceptions about dyslexia concern that led to this work. This paper aims to clarify myths/wrong or less clear ideas about specific learning difficulties in reading - dyslex bibliographical research (used as a data collection technique) carried out as part of the Curricular Unit on Assessment and Intervention in Specific Lea Master's Degree in Special and Inclusive Education, at the School of Education of the Polytechnic Institute of Bragança - Portugal. Establishing a c about the problem, shared by all educational stakeholders, is essential throughout the journey from detecting the risk of dyslexia to diagnosing it.In this sense, based on scientific evidence from literature research, it is possible to systematize, among other myths or misconceptions, that: 1) dyslexia is not synonymous with low intelligence; 2) dyslexia has no cure; 3) dyslexia can be identified early; 4) dyslexia is not a visual problem; 5) children with dyslexia can succeed at school; 6) dyslexia exists in both sexes; 7) not all children who have difficulties learning to read have dyslexia; 8) intervention, although always welcome, should be as early as possible; 9) the adjustments that are made for children with dyslexia at school level do not benefit them in relation to other children and are not unfair to anyo 10) there are early indicators of dyslexia that can give rise to suspicions that it may manifest itself; 11) repeating the school year does not help to overcome dyslexia; 12) diagnosing a child with dyslexia does not label them; 13) not all pupils with dyslexia swap letters, syllables or words with subtle differences in spelling. Therefore, based on our experience of working in a school context, we conclude that there are still a number of misconceptions about dyslexia that n on the basis of scientific knowledge, and not deep-rooted myths, can we prevent and intervene early to avoid serious consequences for the acade and young people with dyslexia. We therefore believe that this work is particularly important for parents and guardians, educators, teachers and tec of an inclusive school and education.